Masculinities and condom use patterns among young rural South Africa men: a cross-sectional baseline survey - Shai N; Jewkes R; Nduna M; Dunkle K (BMC, 2012)
Abstract Background Notions of ideal manhood in South Africa are potentially prescriptive of male sexuality thus accounting for the behaviors which may lead to men being at greater HIV risk. We tested the hypothesis that gender and relationship constructs are associated with condom use among young men living in rural South Africa. Methods 1219 men aged 15-26 years completed a cross-sectional baseline survey from an IsiXhosa questionnaire asking about sexual behaviour and relationships. Univariate and bivariate analyses described condom use patterns and explanatory variables, and multinomial regression modeling assessed the factors associated with inconsistent versus consistent and non-condom use. Results 47.7% of men never used condoms, when 36.9% were inconsistent and 15.4% were consistent with any partner in the past year. Condom use patterns differed in association with gender relations attitudes: never users were significantly more conservative than inconsistent or consistent users. Three gender positions emerged indicating that inconsistent users were most physically/sexually violent and sexually risky; never users had more conservative gender attitudes but were less violent and sexually risky; and consistent users were less conservative, less violent and sexually risky with notably fewer sexual partners than inconsistent users. Conclusions The confluence of conservative gender attitudes, perpetration of violence against women and sexual risk taking distinguished inconsistent condom users as the most risky compared to never condom users, and rendered inconsistent use one of the basic negative attributes of dominant masculinities in the Eastern Cape, South Africa. This finding is important for the design of HIV prevention and gender equity interventions and emphasizes the need for a wider roll-out of interventions that promote progressive and healthy masculine practices in the country.